PENGARUH MEDIA SOSIAL TERHADAP DINAMIKA MASYARAKAT DAN LAHIRNYA BENTUK-BENTUK PERBUATAN HUKUM BARU DI MEDIA SOSIAL - Rizana Rizana; Andrew Shandy Utama; Irene Svinarky (Jurnal Cahaya Keadilan, 2021)
This study aims to explain the influence of social media on the dynamics of society according to the perspective of Sociology of Law and the influence of social media on the birth of new forms of legal action in the Law on Information and Electronic Transactions. The method used in this research is normative legal research, using a statutory approach. The development of information and communication technology has changed human civilization globally. The development of information and communication technology has made the world borderless, resulting in social dynamics in society. Social media on the one hand is private, but on the other hand it is public media because it can be seen by other people. New forms of legal action in the Law on Electronic Information and Transactions, namely distributing and/or transmitting and/or making accessible electronic information and/or electronic documents that have content that violates decency, which has content of gambling, which has insulting content. and/or defamation, and which contains extortion and/or threats. In addition, new forms of legal action in the Law on Electronic Information and Transactions are spreading false and misleading news that results in consumer losses in electronic transactions and disseminating information aimed at causing hatred or hostility to certain individuals and/or community groups based on on ethnicity, religion, race, and intergroup (SARA). Finally, a person can be punished for sending electronic information and/or electronic documents that contain threats of violence or intimidation aimed at personally.